Study of obstetric factors in perinatal morbidity and mortality at a tertiary centre - Tambe, Sanjaykumar G.; Thawal, Yogesh A.; Anand, Tania; Kolate, Dipak Suresh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Safe motherhood and child survival have always been a concern for the policymakers but perinatal mortality, especially stillbirths, have not received due attention. There are 5.9 million perinatal deaths worldwide, almost all of which occur in developing countries. Stillbirths account for over half of all perinatal deaths. This study was aimed to determine perinatal mortality rate and related obstetrics risk factors. Perinatal mortality is only a tip of the iceberg, morbidity being much higher. Vital statistics obtained through this study may serve an important source of information to guide the public health policy makers and health care providers in future. Methods: Present observational study was undertaken in a tertiary center to look into various maternal factors and possible cause of perinatal death. All perinatal deaths including stillbirths (SBs) and early neonatal deaths (ENNDs) within 0-7 days of birth after 28 weeks of gestation were analysed. The data was collected through a pre-designed proforma. Results: Perinatal mortality is 66.27/1000 births in our centre, where 37% were intrauterine deaths, 34% were neonatal deaths and 29% were still births. Preterm, pregnancy induced hypertension; abruptio placentae remain the most important factors for perinatal loss. Conclusions: One of the reasons for high perinatal mortality in tertiary centres is because of poor antenatal care at peripheral centres and late referrals. Early detection of obstetric complications and aggressive treatment is one of golden rule to reduce perinatal loss.